2015
DOI: 10.1088/0004-637x/815/2/88
|View full text |Cite
|
Sign up to set email alerts
|

ON THE DETECTION OF GLOBAL 21-cm SIGNAL FROM REIONIZATION USING INTERFEROMETERS

Abstract: Detection of the global redshifted 21-cm signal is an excellent means of deciphering the physical processes during the Dark Ages and subsequent Epoch of Reionization (EoR). However, detection of this faint monopole is challenging due to the high precision required in instrumental calibration and modeling of substantially brighter foregrounds and instrumental systematics. In particular, modeling of receiver noise with mK accuracy and its separation remains a formidable task in experiments aiming to detect the g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 30 publications
2
43
0
Order By: Relevance
“…This approach is being pursued by the Experiment to Detect the Global EoR Signature (EDGES; Bernardi, McQuinn, & Greenhill 2015), Shaped Antenna measurement of background Radio Spectrum (SARAS Patra et al 2013;Singh et al 2015), and the Dark Ages Radio Explorer (DARE; Burns et al 2012). Both methods require careful and accurate subtraction of the sky foreground since the 21 cm signal is three to five orders of magnitude below the foreground.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is being pursued by the Experiment to Detect the Global EoR Signature (EDGES; Bernardi, McQuinn, & Greenhill 2015), Shaped Antenna measurement of background Radio Spectrum (SARAS Patra et al 2013;Singh et al 2015), and the Dark Ages Radio Explorer (DARE; Burns et al 2012). Both methods require careful and accurate subtraction of the sky foreground since the 21 cm signal is three to five orders of magnitude below the foreground.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental result reported in this manuscript has several implications in optics as well as related areas of research like Radio Astronomy. In the latter, the community is divided in the sense that while some work in available literature seems to take into account boundary condition effects [22,23], there are others which seem to ignore them [24,25]. We have explored this application in further detail and found that by taking relevant parameters from such experiments [25], we get κ to be of the order of 10 −2 which is definitely not ignorable any more considering that here we are reporting an experiment where we have successfully measured the quantity much above the error bound.…”
Section: Approximations Sometimes Made In Astronomymentioning
confidence: 99%
“…The major efforts include the Experiment to Detect the Global EoR Signature (EDGES) (Bowman & Rogers 2010), Dark Ages Radio Explorer (DARE) (Burns et al 2012), Broadband Instrument for Global Hydrogen Reionisation Signal (BIGHORNS) (Sokolowski et al 2015), Shaped Antenna measurement of background Radio Spectrum (SARAS) (Patra et al 2013;Singh et al 2015), Large-aperture Experiment to detect the Dark Age (LEDA) (Bernardi, McQuinn, & Greenhill 2015), and Sonda Cosmológica de las Islas para la Detección de Hidrógeno Neutro (SCI-HI) (Voytek et al 2014). Several studies have addressed experimental calibration issues (Rogers & Bowman 2012;Patra et al 2013;Bernardi, McQuinn, & Greenhill 2015) as well as the frequency dependence of the antenna beams Vedantham et al 2014;Bernardi, McQuinn, & Greenhill 2015).…”
Section: Introductionmentioning
confidence: 99%